2020
DOI: 10.1071/py19081
|View full text |Cite
|
Sign up to set email alerts
|

Provision of palliative and end-of-life care in New Zealand residential aged care facilities: general practitioners' perspectives

Abstract: This exploratory study examined general practitioners’ (GPs) perspectives on delivering end-of-life care in the New Zealand residential aged care context. A general inductive approach to the data collected from semi-structured interviews with 17 GPs from 15 different New Zealand general practices was taken. Findings examine: (1) GPs’ life experience; (2) the GP relationship with the facilities and provision of end-of-life care; (3) the GP interaction with families of dying residents; and (4) GP relationship wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…There are many potential reasons for bereaved families' expressed dissatisfaction in communication with GPs. Firstly, time and cost restraints preclude communicating at length with families [46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many potential reasons for bereaved families' expressed dissatisfaction in communication with GPs. Firstly, time and cost restraints preclude communicating at length with families [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…There are many potential reasons for bereaved families’ expressed dissatisfaction in communication with GPs. Firstly, time and cost restraints preclude communicating at length with families [ 46 , 47 ]. Many of the cases of poor communication and care from GPs from families in this study focused on how communication was handled, and the extent to which GPs showed respect for residents and families.…”
Section: Discussionmentioning
confidence: 99%
“…For GPs, this often means spending only a few hours a week doing rounds in a RAC facility and making decisions for residents within this time (41). As a result, the time available for communicating at length with residents and their families is not available (42). However, many of the cases of poor communication and care from GPs from families in this study focused on the way in which communication was handled, and the extent to which GPs showed respect for residents and families.…”
Section: Discussionmentioning
confidence: 99%
“…Only the views and experiences of bereaved family members are included in these findings. The views of RNs, GPs, HCA's, and PCNSs have been presented elsewhere (4,42,48). Nevertheless, the experiences of these bereaved family members provide both a unique insight into the benefits and challenges to the implementation of SHARE (49).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Only the views and experiences of bereaved family members are included in these ndings. The views of registered nurses, GPs, healthcare assistants, and hospice nurse specialists have been presented elsewhere (4,47,50). Nevertheless, the experiences of these bereaved family members provide both a unique insight into the bene ts and challenges to the implementation of SHARE (51).…”
Section: Strengths and Limitationsmentioning
confidence: 99%